2013
DOI: 10.1021/jp406059h
|View full text |Cite
|
Sign up to set email alerts
|

Water–Gas Shift Reaction on Pt/Ce1–xTixO2−δ: The Effect of Ce/Ti Ratio

Abstract: Pt nanoparticles (1.2−2.0 nm size) supported on Ce 1−x Ti x O 2−δ (x = 0, 0.2, 0.5, 0.8, and 1.0) carriers synthesized by the citrate sol−gel method were tested toward the water−gas shift (WGS) reaction in the 200−350 °C range. A deep insight into the effect of two structural parameters, the chemical composition of support (Ce/Ti atom ratio), and the Pt particle size on the catalytic performance of Pt-loaded catalysts was realized after employing in situ X-ray diffraction (XRD), high-resolution transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 63 publications
1
55
1
Order By: Relevance
“…This in turn resulted in the H 2 evolution rate of 3 wt% Pt/TiO 2 , which was relatively greater than that of 3 wt% Pt/Al 2 O 3 . Other studies found that TiO 2 , as a support material, improves Pt O 2 reduction activity by assisting mechanisms such as reactant surface diffusion and O 2 spillover [135137]. Furthermore, Pt/TiO 2 showed similar performance to Pt/C in H 2 -fuel cell operated at 60°C and 0.8 V (Figure 5) [136].…”
Section: Tio2: As Support In Heterogeneous Catalysismentioning
confidence: 89%
“…This in turn resulted in the H 2 evolution rate of 3 wt% Pt/TiO 2 , which was relatively greater than that of 3 wt% Pt/Al 2 O 3 . Other studies found that TiO 2 , as a support material, improves Pt O 2 reduction activity by assisting mechanisms such as reactant surface diffusion and O 2 spillover [135137]. Furthermore, Pt/TiO 2 showed similar performance to Pt/C in H 2 -fuel cell operated at 60°C and 0.8 V (Figure 5) [136].…”
Section: Tio2: As Support In Heterogeneous Catalysismentioning
confidence: 89%
“…Details of the preparation procedures employed can be found elsewhere [25][26][27]. The metal precursors used were Ce(NO 3 ) 3 ·6H 2 O, Pr(NO 3 ) 3 ·6H 2 O and ZrO(NO 3 ) 2 .xH 2 O (Sigma-Aldrich).…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…The latter may be related to the partial reduction of Ti to Ti 3+ or to the incorporation of cerium in the titania lattice. If we consider that cerium (1.5 Pauling units) is less electronegative than titanium (1.1 Pauling units), the substitution of titanium atoms by cerium in the titania lattice will produce an enhanced electron density on Ti, and consequently, a decrease in binding energy [34]. When the Ce 3d core level ( Figure S3) is considered, six peaks corresponding to the three pairs of spin-orbit doublets of Ce(IV) and two peaks corresponding to the doublet of Ce(III) are observed.…”
Section: Increase Of H 2 Concentration and Addition Of H 2 O And Comentioning
confidence: 99%